EARLY WARNING SYSTEM PADA PEMANTAUAN WILAYAH SEKITAR UNTUK DETEKSI DINI KESEHATAN IBU HAMIL DAN ANAK DI PUSKESMAS PAMULANG - Maulina, Fresty Cahya; Sasykirana, Nasywa; Firmansyah, Miftah Parid; Utama, Timor (STIKes Widya Dharma Husada Tangerang, 2026)
The high Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR) in Indonesia remain critical challenges within the health sector's development. In the Pamulang Public Health Center's working area, this issue is exacerbated by suboptimal data management for extramural Maternal and Child Health (MCH) services, particularly at integrated healthcare centers (Posyandu). Conventional manual recording and reporting practices still predominate, leading to risks of data vulnerability, such as loss, damage, and information fragmentation. Such conditions impede the effectiveness of real-time health monitoring for mothers and children. This study aims to design a web-based extramural service information system to enhance the quality, efficiency, and integration of MCH data. The research employs a qualitative method with a Rapid Application Development (RAD) approach. Data collection was conducted through in-depth observations and semi-structured interviews with healthcare professionals, community health volunteers (kader), and patients. System requirement analysis covers functional and non-functional specifications, represented through system modeling instruments including flowcharts, Data Flow Diagrams (DFD), Entity Relationship Diagrams (ERD), use case diagrams, and user interface designs. The results yield a web-based extramural MCH service information system design that facilitates healthcare providers and volunteers in digitizing examination records, periodic reporting, and longitudinal health progress monitoring. A key advantage of this system is its capacity for integration with the Public Health Center Management Information System (SIMPUS), directly supporting the strengthening of Maternal and Child Health Local Area Monitoring (PWS-KIA). The implementation of this system design is expected to transform data collection and processing from manual to structured digital models. Strategically, the system serves as an accelerative instrument for clinical and administrative decision-making while providing a fundamental reference for primary-level health technology development to significantly reduce maternal and infant mortality.